Game over: o corpo (em) delito na arte contemporânea - Cichelero, Marcos (2015)
This research in visual poetics aims to contribute to the formulation of reflections in contemporary art regarding the production in Art and Technology, through the creation of a gameart called Game Over and the presentation of this as interactive installation. This gameart was produced in immersive and interactive virtual environment, through the free Open Simulator platform that promotes the creation of virtual worlds. These environments are consisted as experimental places in contemporary art, being also called possible worlds and through his presentation in the form of interactive installation, search convergence between the material world and the virtual world. Virtual environments, created by numerical technology, are universes full of singularities to be explored, giving rise to new reflections in the field of art. The game in question will have as its main element body of evidence , which is in essence the criminal fact. Through an examination of body of evidence takes place the criminal forensics to determine the factors that attempt to clarify what has happened. It is intended to relate issues intrinsic to gameart as the simulation and subversion of reality, temporality, among others, issues that arise from the body of evidence and the interaction of this in the digital environment. To clarify the proposition presented in this study, we start from a research in art, through a constant dialogue between the theoretical reflection and artistic practice. Begins this research from one approach to the game concepts and gameart that target the potential of virtual environments and its relation to the body of evidence .